Comparative Analysis of Linguistic, Cultural, and Functional Peculiarities of Aphorisms in D. Trump and V. Putin’s Political Discourse - Kalashova A.S., Patrusheva E.V., Kamensky M.V., Lomteva T.N., Salnikova N.V., (Opción)
The paper focuses on considering from theoretical standpoint linguistic, cultural, and pragmatic aspects of aphorisms functioning in modern political discourse. Scientific data and materials have been obtained as a result of applying the following methods of investigation: continuous sampling method; lexical and semantic analysis method; classification method; quantitative research and deductive reasoning. The paper gives original definitions of the concepts used: political discourse, aphorism, conversational aphorism. In the given article we make an attempt at defining the linguistic status of aphorism and its role in structuring political discourse.